2022
DOI: 10.1186/s40792-022-01467-w
|View full text |Cite
|
Sign up to set email alerts
|

A case of Mirizzi syndrome accompanied by a pseudoaneurysm that ruptured into the gallbladder: successfully treated by embolization of aneurysm and sequential surgery

Abstract: Background Although visceral aneurysms are relatively rare, it can be life-threatening in case it ruptures. We report a case of Mirizzi syndrome accompanied by a pseudoaneurysm that ruptured into the gallbladder. Case presentation The patient was a 73-year-old woman with persistent gastrointestinal bleeding and progressive jaundice. Examination revealed a pseudoaneurysm in the gallbladder artery or hepatic artery branch, and biliary hemorrhage due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To our knowledge, cystic artery pseudoaneurysm in the setting of Mirizzi syndrome has been rarely reported [ 5 7 ]. Suzuki et al [ 5 ] reported an unruptured cystic artery pseudoaneurysm detected on cross-sectional imaging, while the other reported cases were associated with bleeding into the hepatobiliary tract [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, cystic artery pseudoaneurysm in the setting of Mirizzi syndrome has been rarely reported [ 5 7 ]. Suzuki et al [ 5 ] reported an unruptured cystic artery pseudoaneurysm detected on cross-sectional imaging, while the other reported cases were associated with bleeding into the hepatobiliary tract [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to operative management of Mirizzi syndrome and cholecystitis, transarterial embolization (TAE) is useful for the definitive diagnosis and treatment of pseudoaneurysm [ 1 , 6 , 7 , 12 ]. TAE enables prevention of complications associated with visceral artery pseudoaneurysm formation.…”
Section: Discussionmentioning
confidence: 99%